Monitoring Land Surface Temperature (LST) and Land Cover of Basra Province using Remote Sensing Technique and GIS - Kawther Salman; Ban A. Al Razaq (Iraqi Journal of Physics, 2023)
This study investigates the changes occurring in the province of Basra using geospatial methods and analyzes the variations in land surface temperature among the various types of land cover. For the months of July and December in the years 2013 and 2021, Landsat images were used in Landsat 8 OLI/TIRS, and satellite images were processed using ArcGIS 10.8 software. The study's categories for land use and land cover were generated through the application of supervised classification techniques, and the land surface temperature was calculated using data from a satellite sensor's brightness temperature. According to the study's findings, there has been an increase in urban areas (including barren land). From 2013 to 2021, a greater correlation between urban land and LST was found, indicating an increasing surface urban heat island effect as evidenced by its statistically significant correlation coefficients.It has a significant impact on the variations in land surface temperature.This study also highlighted the key variations in how land use and cover affect LST. Across all time periods of investigation. Therefore, techniques for remote sensing and geographic information systems are useful for tracking and analyzing urban expansion patterns and assessing their effects on land surface temperature.